Implementation of Guidance and Supervision of the Authority of Land Deed Making Officials Carried Out by the Head of the Land Office in Badung Regency - Ray Dio Sanjaya; Putu Ayu Sriasih Wesna; I Wayan Kartika Jaya Utama (PT FORMOSA CENDEKIA GLOBAL, 2025)
The Land Deed Official (PPAT) who has been appointed in Badung Regency but continues to work as staff at a notary office in Kalimantan is the background of this research. This study aims to analyze the role and effectiveness of the Advisory and Supervisory Board of PPAT in Badung Regency in carrying out the duties, authorities, guidance, and supervision conducted by the Head of the Land Office of Badung Regency. Using an empirical legal research method, this study explains the gap between norms and practice (das sollen and das sein). The results of the study show that the implementation of the board's duties has been in accordance with the scope of its authority; however, the effectiveness of guidance and supervision still requires additional technical regulations so that the mechanism can function optimally as expected by the government.